Prevalência da ansiedade pré-operatória em crianças e adolescentes de 6 a 14 anos e os fatores associados - Barros, Gabriela Ribeiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Introduction: Preoperative anxiety is a feeling present in most children undergoing anesthetic and surgical procedures, having negative repercussions that affect the entire perioperative period. Thus, it is necessary to identify and measure this feeling in order to direct interventions that reduce it. Objective: To verify the prevalence of preoperative anxiety in children and adolescents aged 6 to 14 years and associated factors. Method: Cross-sectional study carried out from January to December 2020 in children and adolescents aged between 6 and 14 years, ASA (American Society of Anesthesiologists) I or II, undergoing elective surgery for the first time. The Brazilian version of the Children's Anxiety Questionnaire (CAQ) was used to check anxiety and the Visual Analog Scale (VAS) were applied. The variables gender, age, education, surgery, time of the surgical procedure, surgery before or during the Pandemic, ASA (American Society of Anesthesiologists) and place of surgery were considered to verify the association with anxiety. Results: The sample consisted of 98 children in which 72.4% (n=71) were male, 82.7% (n=81) were between 6 and 10 years old, followed by 17.3% (n= 17) from 11 to 14 years old. The most frequent surgical procedures were Postectomy, Adenoidectomy/Tonsillectomy and Herniorrhaphy. The prevalence of anxiety according to the CAQ ≥ 9 was 28.5% (n= 28) and according to the VAS ≥ 7 was 31.6% (n= 31). Conclusion: The prevalence of anxiety according to the CAQ ≥ 9 was 28.5% (n= 28) and according to the VAS ≥ 7 was 31.6% (n= 31), with children undergoing surgical procedures during the pandemic had a lower score for preoperative anxiety according to the CAQ ≥ 9.

Introdução: A ansiedade pré-operatória é um sentimento presente em grande parte das crianças submetidas a um procedimento anestésico e cirúrgico, possuindo repercussões negativas que afetam todo o perioperatório. Dessa forma, é necessário identificar e mensurar tal sentimento a fim de direcionar intervenções que o reduzam. Objetivo: Verificar a prevalência da ansiedade pré-operatória em crianças e adolescentes de 6 a 14 anos e os fatores associados. Método: Estudo Transversal realizado no período de janeiro a dezembro de 2020 em crianças e adolescentes com faixa etária entre 6 a 14 anos, ASA (American Society of Anesthesiologists) I ou II, submetidas a cirurgias eletivas pela primeira vez. Para a verificação da ansiedade aplicou-se a versão Brasileira do Children`s Anxiety Questionnaire (CAQ) e a Escala Visual Analógica (EVA). Foram consideradas as variáveis sexo, idade, escolaridade, cirurgia, tempo do procedimento cirúrgico, cirurgia antes ou durante Pandemia, ASA (American Society of Anesthesiologists) e local da realização da cirurgia, para verificação de associação com a ansiedade. Resultados: A amostra foi composta por 98 crianças nas quais 72,4% (n=71) foram do sexo masculino, 82,7% (n=81) tinham de 6 a 10 anos, seguidos por 17,3% (n=17) de 11 a 14 anos. Os procedimentos cirúrgicos mais frequentes foram Postectomia, Adenoidectomia/Amigdalectomia e Herniorrafia. A prevalência de ansiedade segundo o CAQ ≥ 9 foi de 28,5% (n= 28) e segundo o EVA ≥ 7 foi de 31,6% (n= 31). Conclusão: A prevalência de ansiedade segundo o CAQ ≥ 9 foi de 28,5% (n= 28) e segundo o EVA ≥ 7 foi de 31,6% (n= 31), sendo que as crianças submetidas a procedimentos cirúrgicos durante a pandemia obtiveram menor escore para ansiedade pré- operatória segundo o CAQ ≥ 9.
Prevalence of preoperative anxiety in children and adolescents from 6 to 14 years and associated factors
Keywords: Anxiety; Child; Perioperative Nursing; Ansiedade; Criança; Enfermagem Perioperatória